Islam and Malay Nationalism a case study of the Malay-Muslims of Southern Thailand - Surin Pitsuwan (University Microfilms International, 1982)
Summary: This study focuses on the role of Islam in the movement for cultural and religious autonomy among the Malay-Muslims of Southern Thailand and explores the process of consolidation of power on the part of the Thai government over this minority group